Nanozyme-involved biomimetic cascade catalysis for biomedical applications. (April 2021) - Cai, Xiaoli; Jiao, Lei; Yan, Hongye; Wu, Yu; Gu, Wenling; Du, Dan; Lin, Yuehe; Zhu, Chengzhou
Graphical abstract: Due to the unique physicochemical properties and enzyme-like catalytic activities, nanozymes have been widely explored as alternatives to natural enzymes in biocatalysis, holding great promise in cascade reaction systems. This review highlights the design strategies and the recent advances of nanozyme-involved cascade reactions and their biomedical applications in biosensing, therapy and antioxidation. Abstract: Enzyme cascade reactions in biological systems can effectively improve the catalytic performances owing to their high local concentration, efficient mass transfer and reduced intermediate decomposition. However, the disadvantages of high cost, low stability, and easy inactivation limit their practical applications in harsh environments. Nanozymes as the substitutes for enzymes not only have enzyme-like activities but also possess high stability, tunable catalytic property, and high pH/temperature tolerance, which have been intensively investigated for the establishment of biomimetic catalysis systems. In this review, we first summarized the recent development of the construction and advantage of the nanozyme-involved cascade reaction system. Then, the biomedical applications of the nanozyme-enhanced biomimetic cascade catalytic systems, including biosensing, therapies and antioxidation, were highlighted in detail. Finally, current challenges and future perspectives for nanozyme-activated cascade reactions are discussed and outlooked.